SKRINING DAN PENDAMPINGAN PENCEGAHAN PENYAKIT TIDAK MENULAR DI MASYARAKAT - Nina Indriyawati; Widodo Widodo; Melyana Nurul Widyawati; Djoko Priyatno; Marichatul Jannah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2018)
Increasing the incidence of PTM, it is necessary for education and assistance to the community to carry out early detection or screening of PTM, especially in groups at risk. The target of this community service activity is risky and elderly people as much as 150 people in Demak District, Gubug Sub-district Grobogan District, and District Pudak Payung. evaluation is done by providing a questionnaire about the level of knowledge and monitoring of laboratory results, and blood pressure. Evaluation will be measured from the level of knowledge before and after health education. Increased PTM can be suppressed through the control of risk factors, namely reduction of cigarette, alcohol, sugar and salt consumption, increased consumption of fruits and vegetables, increase physical activity through exercise, prevent obesity, stress control with recreational activities and check blood pressure, regular. Efforts to prevent PTM can be done by the community independently through Posbindu activities.